On Some Desmids from Koshi Tappu Wildlife Reserve, Nepal - Rai, S. K.; Misra, P. K. (Ecoprint: An International Journal of Ecology, 2009)
The present work enumerates a total 26 desmids (Chlorophyta) from ponds and reservoirs in and around Koshi Tappu Wildlife Reserve, Nepal. They belong to 8 genera i.e. Closterium (4), Euastrum (4), Micrasterias (3), Cosmarium (7), Staurastrum (3), Onychonema (2), Hyalotheca (1), and Desmidium (2). Of these, 11 taxa are new records for Nepal. Genus Onychonema is described here for the first time from Nepal. Key words: Algae, chlorophyta, Desmids, Koshi Tappu, Nepal. doi: 10.3126/eco.v15i0.1942 ECOPRINT 15: 47-58, 2008